Microstructure and Mechanical Characteristics of Welded AISI 1020 Low Carbon Steel Based on the Influence of Weld Joint Design and Shielded Metal Arc Welding Process - Samuel Olumide Falana; Isiaka Oladele; Ayodele Olawumi Adedeke; Collins Chidiebere Okoye; Peace Pamilerin Adara; Aladesuyi Kole Aladenika (Journal of Science and Technology, 2025)
This study examines the impact of joint design on the microstructure and mechanical properties of welded AISI 1020 low carbon steel using Shielded Metal Arc Welding (SMAW) with E6013 electrodes. Bevel, butt, and half-lap joints were welded under identical conditions and assessed for mechanical and microstructural performance. The bevel joint exhibited the best overall performance, with improved tensile strength (188.39 MPa), yield strength (113.98 MPa), and impact strength (34.54 J/mm²) compared to butt and half-lap joints due to better weld penetration and load distribution. Microstructural analysis using optical microscope confirmed the presence of distinct ferrite morphologies, including ferrite, Widmanstätten ferrite, and acicular ferrite in the weld metal. The uniform distribution of phases and minimal welding defects in the weld metal zones of the bevel joint further support its mechanical superiority. These results highlight the importance of joint design in optimizing welded steel structures, with the bevel joint proving most suitable for high-strength applications. Hence, the research contributes to the understanding of the effects of joint geometry on welded steel properties and provides practical insights for industrial welding applications.